2018
DOI: 10.1002/lary.27757
|View full text |Cite
|
Sign up to set email alerts
|

Pott's puffy tumor in children: A review of the literature

Abstract: Objectives: Pott's puffy tumor (PTT) is a frontal subperiosteal abscess associated with underlying frontal osteomyelitis. The purpose of the present study was to assess the rate of intracranial involvement in pediatric and adolescent patients with PPT and to discuss the diagnostic workup and the therapeutic features of this pathology.Methods: We searched Web of Science, PubMed and MEDLINE from 1998 to 2018. The search focused on papers concerning the diagnostic procedure and therapeutic management of PTT. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 54 publications
(87 reference statements)
2
52
0
13
Order By: Relevance
“…In a recent review of the literature which included 83 paediatric and adolescent patients surgically treated for PPT, Koltsidopoulos et al, reported that an external approach was used in most of the cases (46.5%), while an endoscopic treatment was used alone in 20% of cases and in combination with an external drainage in 27% of cases. In the remaining cases (3.5%), no surgical treatment was adopted [24]. In another review of the literature published in 2012 including 32 adult patients with PPT after 1990, Akiyama and colleagues reported that external surgical procedure was chosen in 58.1% of the cases, but ESS in combination with an external subperiosteal abscess drainage was adopted in 32.9% of the rest.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of the literature which included 83 paediatric and adolescent patients surgically treated for PPT, Koltsidopoulos et al, reported that an external approach was used in most of the cases (46.5%), while an endoscopic treatment was used alone in 20% of cases and in combination with an external drainage in 27% of cases. In the remaining cases (3.5%), no surgical treatment was adopted [24]. In another review of the literature published in 2012 including 32 adult patients with PPT after 1990, Akiyama and colleagues reported that external surgical procedure was chosen in 58.1% of the cases, but ESS in combination with an external subperiosteal abscess drainage was adopted in 32.9% of the rest.…”
Section: Discussionmentioning
confidence: 99%
“…Acute sinusitis lasts less than 12 weeks and it is usually caused by rhinoviruses, parainfluenza and influenza virus. Chronic sinusitis lasts more than 12 weeks and it is usually caused by anaerobes, gram-negative bacteria, Staphylococcus aureus , and fungi [4].…”
Section: Discussionmentioning
confidence: 99%
“…PPT is classically associated with osteomyelitis of the frontal bone secondary to frontal BARS or trauma 80 . Localized frontal swelling is the most common clinical finding and PPT frequently develops after a misdiagnosed or inadequately treated frontal BARS 81 . The diagnosis of PPT is based on history and clinical and imaging findings (Fig 12).…”
Section: Osseous Complicationsmentioning
confidence: 99%
“…The diagnosis of PPT is based on history and clinical and imaging findings (Fig 12). CT is the imaging modality of choice to confirm the diagnosis 81 . The prevalence of PPT has decreased in the postantibiotic era, however, it may cause potentially devastating complications including preseptal and orbital cellulitis.…”
Section: Osseous Complicationsmentioning
confidence: 99%